Enhancing English Learning in an Islamic University Context: Identifying and Addressing Key Challenges - Angraeni, Lusy; Rosmiaty, Rosmiaty; Chuzaimah, Chuzaimah; Nur, Sitti Rahmani (ELT Worldwide: Journal of English Language Teaching, 2024)
This study explores the factors contributing to students' difficulties in achieving effective English learning at the Muslim University of Indonesia (UMI) and identifies strategies to overcome these challenges. Utilizing a qualitative descriptive research design, data were collected through observations, interviews, and documentation with five fifth-semester students from the English Department. The findings reveal six critical barriers: lack of practice, vocabulary deficiency, environmental factors, lack of interest, low self-confidence, and pronunciation challenges. These factors significantly hinder students' English language proficiency, which is essential for their academic and professional success. The study suggests targeted interventions, including increasing practice opportunities, enhancing vocabulary instruction, creating supportive learning environments, tailoring materials to students' interests, building confidence, and improving pronunciation practice. The implications of these findings highlight the need for comprehensive and context-specific strategies in English as a Foreign Language (EFL) education. Future research should further investigate these areas, considering alternative interpretations and the long-term impact of these factors on language proficiency. By addressing these challenges, educators and policymakers can enhance English language education and support students in achieving their full potential.